Los cuatrocientos golpes - Truffaut, François 1932-1984; Maurier, Claire; Rémy, Albert; Léaud, Jean Pierre (Barcelona Regia Films, 2011)
Intensely touching story of a misunderstood young adolescent who left without attention, delves into a life of petty crime
Idioma: Castellano, francés. Sub.: castellano
Jean Pierre Léaud, Claire Maurier, Albert Rémy... [et al.]
Francia, 1959
Apta para todos los públicos
Doblada al español
Keywords: Películas cinematográficas -- DVD